“Please, may I?”: An analysis of request politeness strategy in online student-supervisor interaction - Wahyuni, Luh Gede Eka; Laksana, I Putu Yoga; Putra, I Nyoman Adi Jaya (Journal of Applied Studies in Language, 2025)
This research examines the various ways in which EFL students and supervisors utilize politeness strategies when making requests in the process of thesis supervision through WhatsApp group communication. The study focuses on how factors such as power dynamics, social distance, and imposition influence the choice of linguistic strategies for making requests. A document study was employed to collect the data. The document was gathered from WhatsApp conversations between 26 students and 5 supervisors and analyzed using Blum-Kulka and Olshtain's situational classification and Brown and Levinson's politeness theory. The findings reveal that students tend to employ more negative politeness strategies, such as questioning, apologies, and expressions of gratitude when making requests to supervisors in order to mitigate potential threats to face. On the other hand, supervisors, due to their higher status positions, tend to use more direct strategies, such as obligations and imperatives, when making requests to students. However, the context also plays a role as supervisors exhibit politeness by using politeness markers in intra-supervisor requests. It concludes that power dynamics, social distance, and imposition ranking significantly influence the selection of politeness strategies, with wider power gaps leading to more negative strategies while familiar relationships foster direct communication. These findings suggest that understanding appropriate politeness strategies can enhance effective communication between students and supervisors and minimize potential miscommunication in cross-cultural academic environments.